Laparoscopy versus open surgery for advanced and resectable gastric cancer: a meta-analysis Laparoscopia versus cirugía abierta en el cáncer gástrico avanzado y resecable: una meta-análisis - David Martínez-Ramos; Juan Manuel Miralles-Tena; Miguel A. Cuesta; Javier Escrig-Sos; Donald van der Peet; Jane S. Hoashi; José Luis Salvador-Sanchis (Revista Espanola de Enfermedades Digestivas, 2011)
Background: there are few studies in the literature comparing laparoscopic versus open Gastrectomy, predominantly for advanced gastric cancer (AGC). Most of the available studies and meta-analysis compare both approaches in the early gastric cancer. The meta-analysis, here presented, compares the clinical outcomes between these two procedures for AGC. Objectives: to evaluate the current status of both partial and total laparoscopic gastrectomy (LG), with regard to its short and long-term outcomes by comparing it to conventional open gastrectomy (OG) for AGC. Data sources and review methods: original articles published in English language from January 1991 to October 2009 were searched in the Medline, Embase, Current Contents, Science Citation Index databases and Cochrane Controlled Trials Register. All articles comparing LG and OG for AGC were included, and those comparing outcomes only for early gastric cancer (EGC) were excluded. Clinical appraisal and data extraction were conducted independently by 3 reviewers. Statistical analysis was carried out following the DerSimonian-Laird random effects model. Results: out of 2,344 studies, 7 studies were selected. One prospective randomized controlled trial, one comparative prospective study and five comparative retrospective studies were analyzed. These studies include a total of 452 patients with gastric cancer, 174 patients in the LG and 278 in the OG. The analyzed result variables were operative time, operative blood loss, hospital postoperative stay, number of dissected lymph nodes and cancer-related mortality risk. Compared to OG, LG was a longer procedure: weighted mean difference (WMD) 44 minutes; 95% confidence interval (CI) 20 to 69; I-squared = 91.6%, but was associated with a lower blood loss (WMD -122 cc; 95% CI -208 to -37; I-squared = 90.8%); this was more significant for hospital operative stay (WMD -6.2 days; 95% CI -9.4 to -2.8; I-squared = 67.8%). Moreover there were no significant differences between the two groups concerning the number of dissected lymph nodes (WMD -1.57; 95% CI -3.41 to 0.26; I-squared = 8.3) and no significant differences for cancer-related mortality risk (adjusted for 60 months of follow-up) although there was a tendency toward a protective effect for LG (Odds Ratio 0.53; 95% CI 0.23 to 1.22; I-squared 41%). Conclusion: laparoscopic total and partial gastrectomy for AGC is associated with a longer operative time but lower blood loss and shorter postoperative hospital stay. Moreover there were similar outcomes between both approaches in terms of number of dissected lymph nodes and long-term follow-up (survival).